THE EFFECTIVENESS OF BRAIN BASED LEARNING MODEL USING SCIENTIFIC APPROACH IN MATHEMATICS LEARNING OF GRADE VIII STUDENTS AT SMPN 4 SUNGGUMINASA IN GOWA DISTRICT - Niswani, Niswani (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2016)
This study aimed at describing the effectiveness of the implementation of brain-based learning model using scientific approach in Mathematics learning of grade VIII students at SMPN 4 Sungguminasa of Gowa District. This study employed pre-experiment research. The population was the entire students of grade VIII at SMPN 4 Sungguminasa of Gowa District. The sample is selected by employing cluster random sampling and obtained grade VIII B as the experiment class. Data collection consists of data of students’ activity in learning, data of students’ learning creativity in Mathematics, and data of students’ response on learning. Data were analyzed using descriptive analysis and inferential analysis. The instrument used in this study were observation sheet on learning implementation, observation sheet on students’ activity, learning test result to measure cognitive ability and learning activity on Mathematics, and questionnaire of students’ response. The results of study reveal that the students’ activity is in very good category by the mean score 3.6, the students’ learning outcome is in high category by the mean score 80.93 and the deviation standard 6.95, the classical completeness degree is 91%, the normalized gain of learning outcome is in high  category, the students’ learning creativity result is in fair category by the mean score 66.18, the normalized gain of students’ learning creativity is in fair category, the students’ response on the implementation of brain-based learning model with scientific approach is in positive category by the mean score 3.6. In general, the conclusion of the study is the brain-based learning model using scientific approach in Methematics learning of grade VIII students at SMPN 4 Sungguminasa in Gowa district is implemented effectively